Disruptive behavior disorders and indicators of disinhibition in adolescents: The BRIEF‐SR, anti‐saccade task, and D‐KEFS color–word interference test. (14th August 2015) - Long, E.C.; Hill, J.; Luna, B.; Verhulst, B.; Clark, D.B.
Abstract: Disinhibition contributes to the development of disruptive behavior disorders (DBD) in adolescents. Self‐reports and behavioral tasks are commonly used to assess disinhibition, each with their unique strengths and limitations. Accordingly, it is important to identify which measure, or combination thereof, is the most effective in predicting DBD symptoms. This study assessed the relationship between DBD (symptoms of ADHD/ODD/CD) and two behavioral disinhibition tasks: the anti‐saccade task and the D‐KEFS color–word interference test, as well as a self‐report measure (the BRIEF‐SR). The results indicated that the BRIEF‐Inhibit scale accounted for the majority of the variance in the DBD sum score. The anti‐saccade task and color–word interference test were also significantly associated with an increase in the number of DBD symptoms endorsed. These behavioral tasks accounted for 9% additional variance than the self‐report alone. Therefore, combining self‐report measures with behavioral disinhibition tasks may provide the most thorough assessment of adolescent DBD.